Comparing the consequences of natural selection, adaptive phenotypic plasticity, and matching habitat choice for phenotype–environment matching, population genetic structure, and reproductive isolation in meta‐populations. Issue 8 (13th March 2018) - Nicolaus, Marion; Edelaar, Pim
Abstract: Organisms commonly experience significant spatiotemporal variation in their environments. In response to such heterogeneity, different mechanisms may act that enhance ecological performance locally. However, depending on the nature of the mechanism involved, the consequences for populations may differ greatly. Building on a previous model that investigated the conditions under which different adaptive mechanisms (co)evolve, this study compares the ecological and evolutionary population consequences of three very different responses to environmental heterogeneity: matching habitat choice (directed gene flow), adaptive plasticity (associated with random gene flow), and divergent natural selection. Using individual‐based simulations, we show that matching habitat choice can have a greater adaptive potential than plasticity or natural selection: it allows for local adaptation while protecting genetic polymorphism despite global mating or strong environmental changes. Our simulations further reveal that increasing environmental fluctuations and unpredictability generally favor the emergence of specialist genotypes but that matching habitat choice is better at preventing local maladaptation by individuals. This confirms that matching habitat choice can speed up the genetic divergence among populations, cause indirect assortative mating via spatial clustering, and hence even facilitate sympatric speciation. This study highlights the potential importance of directed dispersal in local adaptation and speciation, stresses the difficulty of deriving its operation from nonexperimental observational data alone, and helps define a set of ecological conditions which should favor its emergence and subsequent detection in nature. Abstract : Organisms commonly experience significant spatiotemporal variation in their environment, and populations can respond to this via different mechanisms that enhance individual local performance. Using individual‐based simulation modeling, we compared the ecological and evolutionary population consequences of matching habitat choice (directed gene flow) with those of more familiar mechanisms: adaptive plasticity (associated with random gene flow) and divergent natural selection. We confirm that matching habitat choice can speed up local adaptation and genetic divergence among populations and can cause indirect assortative mating via spatial clustering and hence facilitate sympatric speciation.